Membangkitkan Kembali Olahraga Tradisional Di Era Digital: Implementasi UU No 5 Tahun 2017 Tentang Pemajuan Kebudayaan - Tri Setyo Guntoro; Dewi Nurhidayah; Sutoro Sutoro; Astini Asri; Miftah Fariz Putra; Evi Sinaga (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The government's efforts to increase cultural resilience in the digital era are carried out with Law No. 5 of 2017 concerning the promotion of culture. One of the objects for promoting culture based on this law is traditional sports. The purpose of this service is to introduce and preserve traditional sports from Papua, namely nenggi kenggi, morning towe, ninanogum paga, agabolo coconut, and tok-tok to the younger generation. This service is carried out as a form of participation in efforts to promote culture which is also in line with the mission of Cenderawasih University, which is to develop science and technology based on culture and environment. The methods used in the service are lectures and demonstrations which are packaged in the form of outreach. Partners in this service are the upper class students of SD Negeri Inpres Prumnas 1 Waena consisting of 50 students. The stages in this community service consist of four stages, namely discussions with partners, designing activity arrangements and socialization materials, implementing community service activities, monitoring and evaluation. Evaluation of activities is carried out by looking at the achievement of the service carried out. Data analysis techniques use descriptive statistics with percentage formulas. The results showed that there was a change in students' understanding from those who did not know to know. Nenggi kenggi games, morning towe, ninanogum paga, agabolo coconuts, and tok-tok can be practiced well by students. This game can be an option for children to reduce smartphone use.)